A revision of the wax scale insects (Hemiptera: Sternorrhyncha: Coccoidea: Ceroplastinae) of the Afrotropical Region - Hodgson, Chris J.; Peronti, Ana L. B. G. (Zootaxa, 2012)
This paper reviews all species within the scale insect subfamily Ceroplastinae (Hemiptera: Sternorrhyncha: Coccoidea:Coccidae) known from the Afrotropical Region (here including the whole of Africa, the Atlantic islands of Azores,Madeira, Canary Is., São Tomé, Principe, and Cape Verde Is., and the Indian Ocean islands of Madagascar, Seychelles,Mauritius, Réunion, Comoros, and Aldabra). At the start of the review, there were 64 species of wax scale insects andsubspecies in 4 genera recorded from this area. This paper describes or redescribes 58 species, 9 of them new, andsynonymises 18 species. We consider that these species are best placed in 19 species-groups and 2 genera, CeroplastesGrey and Waxiella De Lotto, based on adult female morphology. Only 1 species and 1 subspecies previously recordedfrom Africa have not been seen (Waxiella erithraeus (Leonardi) and Waxiella mimosae neghelli (Bellio)). The preciseidentity of species close to C. rusci (Linnaeus) in Africa still requires further study, probably using molecular analysis asseveral records are considered to refer to cryptic or sibling species. The records of C. ceriferus (Fabricius) and C.actiniformis Green from Africa are considered to be misidentifications. The new species are: C. balachowskyi Hodgson& Peronti spec. nov., C. danieleae Hodgson & Peronti spec. nov., C. delottoi Hodgson & Peronti, spec. nov., C. elaeisHodgson & Peronti, spec. nov., C. ghesquierei Hodgson & Peronti spec. nov., C. jos Hodgson & Peronti spec. nov., C.mori Hodgson & Peronti spec. nov., C. neobrachystegiae Hodgson & Peronti spec. nov. and C. newsteadi Hodgson &Peronti spec. nov. The new synonymies are: Ceroplastes longicauda sapii Hall syn. nov of C. longicauda Brain.;Ceroplastes candela Cockerell & King syn. nov. of Gascardia madagascariensis Targioni Tozzetti (now in Ceroplastes);C. combreti Brain syn. nov. of G. madagascariensis; C. uapacae Hall syn. nov. of C. personatus Newstead; C.vinsonioides Newstead syn. nov. of C. personatus; C. fumidus De Lotto syn. nov. of Coccus rusci Linnaeus (now inCeroplastes); C. hololeucus De Lotto syn. nov. of C. singularis Newstead; C. spicatus Hall syn. nov. of C. eucleae Brain;C. coniformis Newstead syn. nov. of C. theobromae Newstead; C. constricta De Lotto syn. nov. of C. lamborni Newstead;Ceroplastes egbarum fulleri Cockerell & Cockerell syn. nov. of C. egbara Cockerell (now in Waxiella); Ceroplastesegbarum rhodesiensis Hall syn. nov. of C. egbara; Ceroplastes martinoi Almeida syn. nov. of C. egbara; Ceroplastesugandae Newstead syn. nov. of C. egbara; Ceroplastes zonatus Newstead syn. nov. of C. egbara; Ceroplastes berliniaeHall syn. nov. of C. subsphaerica Newstead (now in Waxiella); Ceroplastes berlineae enkeldoorni Hall syn. nov. of C.subsphaerica; and Waxiella tamaricis Ben-Dov syn. nov. of C. mimosae Signoret (now in Waxiella). A neotype isdesignated for Coccus rusci Linnaeus (now Ceroplastes rusci (L.)). The subspecies Ceroplastes africanus senegalensisMarchal is here raised to specific rank and transferred to Waxiella as W. senegalensis (Marchal) stat. nov. Ceroplastesluteolus De Lotto, previously synonymised with C. brevicauda Hall, and C. tenuitectus Green, previously synonymisedwith C. rusci (L.), are here accepted as good species (stat. rev.). Ceroplastes cirripediformis Comstock is recorded fromAfrica (South Africa) for the first time. Waxiella uvariae (Marchal) is transferred back to Ceroplastes as C. uvariaeMarchal stat. rev. Due to the large number of synonymies introduced here and in order to stabilise the status of some ofthe species, lectotypes have been designated for the following species: C. afrinanus senegalensis Marchal; C. berliniae Hall; C. berliniae enkeldoorni Hall; C. bipartitus Newstead; C. brevicauda Hall; C. coniformis Newstead; C. egbarumfulleri Cockerell & Cockerell; C. egbarum rhodesiensis Hall; C. elytropappi Brain; C. eucleae Brain; C. eugeniae Hall;C. ficus Newstead; C. galeatus Newstead; C. helichrysi Hall; C. lamborni Newstead; C. longicauda Brain; C. personatusNewstead; C. quadrilineatus Newstead; C. quadrilineatus simplex Brain; C. quadrilineatus royenae Hall; C. singularisNewstead; C. sinoiae Hall; C. tachardiaformis Brain; C. tenuitectus Green; C. toddaliae Hall; C. toddaliae spicatus Hall;C. uapacea Hall; C. uapacea chrysophyllae Hall; C. ugandae Newstead; C. uvariae Marchal; C. vinsonioides Newstead;C. vuilleti Marchal and C. zonatus Newstead. Keys are provided to identify the 19 species-groups recognised from thearea here studied and to all species in each species-group. There is a short final discussion, including such topics as thedistribution and the relationships of the species found on the Atlantic and Indian Ocean Islands. Maps are providedshowing the country distribution of each of the species covered and a list of plant species known as host of Ceroplastinae in the Afrotropical Region is appended.